2019
DOI: 10.1093/nar/gkz141
|View full text |Cite
|
Sign up to set email alerts
|

circ-Sirt1 controls NF-κB activation via sequence-specific interaction and enhancement of SIRT1 expression by binding to miR-132/212 in vascular smooth muscle cells

Abstract: NF-κB-mediated inflammatory phenotypic switching of vascular smooth muscle cells (VSMCs) plays a central role in atherosclerosis and neointimal formation. However, little is known about the roles of circRNAs in the regulation of NF-κB signaling. Here, we identify the involvement of circ-Sirt1 that was one of transcripts of SIRT1 host gene in VSMC inflammatory response and neointimal hyperplasia. First, in the cytoplasm, circ-Sirt1 directly interacts with and sequesters NF-κB p65 from nuclear translocation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(109 citation statements)
references
References 42 publications
5
104
0
Order By: Relevance
“…Of note, not all circRNAs function as miRNA sponges in cells. At present, several functional models of circRNAs have been reported: (1) circRNAs function as miRNA sponges, which competitively bind endogenous miRNAs; (2) circRNAs function as “protein scaffolds,” which means that circRNAs directly bind to proteins and maintain the stability of the protein complex; 39 , 40 , 41 , 42 and (3) some circRNAs can be translated as “coding RNAs,” which means that they directly encode a protein or peptide. 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Due to the lack of free ends, circRNAs are resistant to exonucleases and more stable than their linear isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, not all circRNAs function as miRNA sponges in cells. At present, several functional models of circRNAs have been reported: (1) circRNAs function as miRNA sponges, which competitively bind endogenous miRNAs; (2) circRNAs function as “protein scaffolds,” which means that circRNAs directly bind to proteins and maintain the stability of the protein complex; 39 , 40 , 41 , 42 and (3) some circRNAs can be translated as “coding RNAs,” which means that they directly encode a protein or peptide. 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Due to the lack of free ends, circRNAs are resistant to exonucleases and more stable than their linear isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…2C) (50). For instance, circ-Sirt1 interacts with NF-κB p65 in the cytoplasm, thereby sequestering the nuclear translocation of p65 (induced by inflammation), and inhibiting the expression of inflammatory factors (51). circRNAs are considered to serve as protein scaffolds by harbouring binding sites for the assembly of two or more proteins, such as enzymes and their substrates, which may subsequently form large protein complexes (37).…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…CircACTA2 competitively binds miR‐548f‐5p, which suppresses the expression of α‐SMA in VSMCs, and is involved in hypertension . Our group demonstrated that circ‐Sirt1 controls NF‐κB activation via a sequence‐specific interaction with p65 and enhancement of SIRT1 expression by sponging miR‐132/212 in the inflammatory phenotypic transformation of VSMCs . Liu et al found that the expression of circRNA‐ZNF609, a sponge for miR‐615‐5p, has a negative correlation with the velocity of vascular endothelial cell migration and tube formation and is associated with vascular endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 65%